Peranan Komunikasi, Lingkungan Kerja Dan Kompensasi Terhadap Kinerja Karyawan Dengan Semangat Kerja Sebagai Variable Intervening Dimasa Pandemi Covid-19 (Studi Kasus Pada Karyawan PT Eka Prima Mandiri Sentosa) - Ighfirlana Ighfirlana; Rois Arifin; M Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThis study aims to determine the role of communication, work environment and compensation on employee performance with morale as an intervening variable. The population in this study were all employees of PT. Eka Prima Mandiri Sentosa-Surabaya Branch. The sample in this study was 58 respondents. Data was collected by distributing questionnaires, interviews and documentation. Analysis of the data used in this study using validity, reliability, normality, path analysis, t test and Sobel test.The results showed that communication did not play a direct role in morale. While the work environment and compensation play a direct role in morale. Communication does not play a direct role in employee performance. Meanwhile, the work environment and compensation have a direct role in employee performance. Morale plays a direct role in employee performance. Communication plays a direct role in employee performance with morale as an intervening variable. While the work environment and compensation variables play an indirect role on employee performance with work enthusiasm as an intervening variable. Keywords : Communication, Work Environment, Compensation, Employee Performance, Morale